ZYA CBT as a Digital Evaluation Tool for Enhancing Authentic Assessment Practices in Education - Shofia Istiqomah; Muhammad Munif (Education and Sociedad Journal, 2024)
This study aims to analyze the implementation of ZYA CBT-assisted learning evaluation in enhancing teachers’ authentic assessment practices in Islamic Religious Education. This research employed a qualitative approach using a multi-case study design. Data were collected through classroom observations, in-depth interviews, and documentation. The collected data were analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of ZYA CBT-assisted learning evaluation consists of three major stages: planning, implementation, and evaluation. In the planning stage, teachers in both educational institutions prepared assessment blueprints, test items, answer keys, and scoring systems. During the implementation stage, both institutions utilized the same ZYA CBT application and examination facilities. Several procedural steps were followed by students during the examination process to ensure the effectiveness of the evaluation. In the evaluation stage, teachers and institutions reviewed technical obstacles encountered during the implementation process and analyzed assessment results generated automatically through the ZYA CBT system. The implementation of ZYA CBT-assisted learning evaluation produced positive implications for institutions, teachers, and students. The use of digital-based evaluation not only introduced technological adaptation in the learning process but also strengthened teachers’ authentic assessment practices in evaluating students’ competencies more effectively and efficiently.